Luttinger model : the first 50 years and some new directions - Mastropietro, Vieri; Mattis, Daniel Charles, 1932- editor (New Jersey ; London ; Singapore ; Beijing ; Shanghai ; Hong Kong ; Taipei ; Chennai : World Scientific, 2014)
Includes bibliographical references